Analysis of Entrepreneurial Motivation on Entrepreneurial Psychology in the Context of Transition Economy - Shi, Baisheng; Wang, Tao (Frontiers in Psychology, 2021)
The purposes are to explore the connotation of entrepreneurial motivation in the context of the transition economy and analyze the influence of entrepreneurial motivation on entrepreneurial psychology. Under China’s current transition economy environment, the theoretical analysis and empirical research are combined. The actual situations of 135 young entrepreneurs are investigated through questionnaire surveys and interviews. Theoretical analysis and practical research are performed on entrepreneurial psychology, entrepreneurial environment, and entrepreneurial motivation. Finally, the influences of different entrepreneurial motivation factors on entrepreneurial psychology are analyzed. Results demonstrate that of the 135 research samples, male entrepreneurs account for 88.1%, while the female entrepreneurs only occupy 11.9%. Entrepreneurs aged 25-29 account for 40.7% of the total; most of them have academic qualifications of undergraduate or postgraduate. The item of “gain wealth” on the entrepreneurial motivation scale has the highest score of 3.98 points. In contrast, the scores of opportunity motivation and survival motivation are basically the same, with great differences between different individuals. The dimensions of policies, regulations, and government functions on the entrepreneurial environment scale have high ranks and levels, while the support of industry associations needs to be strengthened. Generally, the entrepreneurial psychology scale has high scores; most of the items score above 3.45 points, indicating that entrepreneurship not only improves the quality of work and life for young entrepreneurs but also promotes the personal growth of entrepreneurs. The multiple stepwise regression analysis reveals significant correlations between young entrepreneurs’ survival motivation and opportunity motivation and their subjective psychology and social psychology. The results can provide experimental and useful reference materials for the following investigations.